Preparation method and application of magnetic molecularly imprinted material capable of selectively adsorbing limonin
By preparing the magnetic molecular imprinting material of limonosin, using Fe3O4@SiO2-COOH carrier and methacrylic acid and other functional monomers, the problem of insufficient selectivity for limonosin removal and loss of nutrients in citrus juice was solved, and efficient and highly selective limonosin adsorption and removal were achieved, retaining the nutrients of the juice.
Patent Information
- Application Number
- CN202510069173.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-01
Smart Images

Figure CN119733492A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adsorption and separation materials, and particularly relates to a molecular imprinting material for adsorbing limonin, a preparation method and application thereof. Background Art
[0002] Juice processing is an important way to increase the added value of citrus, but the bitterness caused by limonoid compounds (tetracyclic triterpenoid secondary metabolites) limits the development of this industry. To solve this problem, a variety of citrus debittering studies based on physical and chemical methods and biotechnology have been carried out at home and abroad. Biological debittering mainly uses microorganisms or enzymes produced by them to degrade / convert bitter substances. Due to the poor stability of enzymes, strict control of process parameters, and insufficient knowledge of related molecular biology, biological debittering is difficult to be widely used in industrial production in the short term. The resin adsorption method in the physical and chemical method has become the preferred method for debittering citrus because of its easy handling, regeneration and long-term use. However, the resin adsorption method has the problem of insufficient selectivity, and the loss of nutrients is often accompanied by the removal of bitterness. Improving the specificity and orientation of debittering technology is an important direction for future development in this field.
[0003] Molecularly imprinted polymers (MIPs) are a type of smart adsorbent material inspired by nature, which are prepared by polymerization reactions of crosslinkers and functional monomers in the presence of template / target molecules. After the template is removed, binding sites with specific cavities are generated, which are complementary to the target molecules in shape, size and functional groups. As a directed constructed polymer, MIPs show excellent predetermined selectivity in recognizing specific targets and can selectively adsorb based on customized binding cavities and non-covalent chemical interactions (such as π-π interactions, hydrogen bonds, ionic interactions, van der Waals forces, etc.) or reversible covalent bonds. Due to their high selectivity, high stability and easy preparation, MIP materials have attracted extensive research in the adsorption, recovery and removal of specific substances in food.
[0004] At present, there are few studies on the design, preparation and adsorption mechanism analysis of limonin molecular imprinting polymers. Limonin is a triterpenoid compound containing a lactone group. Literature search found that various triterpenoid-related molecular imprinting materials have been successfully developed, and the lactone group can be used as a recognition group. These studies provide a theoretical basis and technical support for the design and optimization of limonin molecular imprinting adsorption materials. The development of limonin molecular imprinting polymers may provide a new technical path for solving the bitterness problem of citrus juice. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing a limonin molecularly imprinted polymer. The limonin molecularly imprinted polymer prepared by the method is used for adsorbing and removing limonin from fruit juice, and compared with traditional adsorption materials, the limonin molecularly imprinted polymer has better specificity and directionality.
[0006] In order to achieve the above-mentioned invention object, the specific technical scheme is as follows:
[0007] A method for preparing a limonin magnetic molecular imprinting material comprises the following steps:
[0008] S1.Fe3O4@SiO2 magnetic particles: After fully mixing the ethanol aqueous solution and NH3·H2O, add Fe3O4 and disperse it evenly by ultrasound. Slowly add the mixture of ethyl orthosilicate and ethanol and mechanically stir it at 50℃ for 10h. After the reaction is completed, separate the product by magnetic force, wash it repeatedly with ethanol and water, and vacuum dry it at 35℃ for 12h to obtain Fe3O4@SiO2 magnetic particles.
[0009] S2.Fe3O4@SiO2-COOH magnetic particles: The Fe3O4@SiO2 prepared in S1 was dispersed in anhydrous toluene, ultrasonically mixed, and then 3-aminopropyltriethoxysilane was added. The mixture was refluxed at 110°C for 12 hours under dry nitrogen. After the reaction, the obtained material was washed with toluene and DMF, then evenly dispersed in DMF, and then maleic anhydride was added. The obtained mixture was mechanically stirred at room temperature for 12 hours. The obtained product was magnetically separated and washed with DMF three times to obtain Fe3O4@SiO2-COOH.
[0010] S3. Limonin magnetic molecular imprinting material: Limonin and methacrylic acid were dispersed in acetonitrile and oscillated for 6 hours for prepolymerization. Then, Fe3O4@SiO2-COOH prepared in S2, ethylene glycol dimethacrylate and azobisisobutyronitrile were added, and the mixed solution was purged with nitrogen for 10 minutes under an ice bath and sealed. A two-step temperature polymerization reaction was carried out in a constant temperature oscillator at a rate of 200r / min: first, polymerization at 50°C for 6 hours, and then polymerization at 60°C for 24 hours. After the reaction, the residual reagents on the surface of the obtained material were washed with acetonitrile, and then the limonin therein was eluted with a mixture of methanol and acetic acid. Finally, the material was rinsed with water and dried at 35°C for 12 hours to obtain a limonin magnetic molecular imprinting material.
[0011] Preferably, the volume ratio of ethanol to water in the ethanol aqueous solution in S1 is 4:1; the volume of the ethanol aqueous solution is 0.45 L / g based on the mass of Fe3O4; the amount of NH3·H2O is 8 mL / g based on the mass of Fe3O4; the volume of tetraethyl orthosilicate is 6 mL / g based on the mass of Fe3O4; and the volume ratio of tetraethyl orthosilicate to the ethanol mixed solution is 1:10.
[0012] Preferably, the volume amount of toluene in S2 is 80 mL / g based on the mass of magnetic nano-microspheres Fe3O4@SiO2; the volume amount of 3-aminopropyltriethoxysilane is 5 mL / g based on the mass of magnetic nano-microspheres Fe3O4@SiO2; the mass amount of maleic anhydride is 1.5 g / g based on the mass of magnetic nano-microspheres Fe3O4@SiO2; and the volume amount of DMF is 80 mL / g based on the mass of magnetic nano-microspheres Fe3O4@SiO2.
[0013] Preferably, the volume of acetonitrile in S3 is 200 mL / mmol based on the amount of the template molecule.
[0014] Preferably, the ratio of the amount of the template molecule, methacrylic acid and the cross-linking agent in S3 is 1:4:16; the mass amount of the initiator is 6 mg / g based on the mass of the cross-linking agent; the mass amount of Fe3O4@SiO2-COOH is 400 mg / mmol based on the amount of the template molecule; and the volume ratio of the methanol and acetic acid mixture is 9:1.
[0015] The invention discloses application of the limonin magnetic molecular imprinting material in debittering citrus juice.
[0016] Preferably, the limonin magnetic molecular imprinting material is added to citrus juice for adsorbing limonin; the added amount of the limonin magnetic molecular imprinting material is 5 mg / mL.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] 1. The present invention prepares a magnetic molecular imprinting material that can selectively adsorb limonin, providing a new technical path for debittering citrus juice.
[0019] 2. The present invention uses Fe3O4 as the core and performs silicon coating and functional modification on its surface, which can not only make the magnetic particles more stable and less prone to oxidation, but also improve the efficiency and stability of molecular imprinting polymers generated on the particle surface.
[0020] 3. The present invention uses methacrylic acid as a functional monomer, utilizes the electrostatic interaction, hydrogen bonding and other interaction forces generated by the ester group of limonin, and generates a polymer with a spatial network structure under the fixation of a crosslinking agent. After eluting the limonin, a cavity that matches the physical size of the limonin and can generate interaction forces with the limonin is exposed, thereby realizing the construction of a molecular imprinting material that specifically binds to limonin.
[0021] 4. The limonin magnetic molecular imprinted material prepared by the present invention belongs to a surface-type imprinted material, characterized in that the imprinted sites are mainly distributed on the outer surface of the particles, thereby greatly reducing the diffusion resistance of the target molecules. The template molecules can quickly enter and leave the imprinted holes, showing excellent adsorption rate and capacity.
[0022] 5. The limonin magnetic molecular imprinted material of the present invention has superparamagnetism. Under the directional control of the external magnetic field, the target molecules can be quickly separated from the juice system, eliminating the complicated operations such as centrifugation and filtration, and bringing great convenience to the separation and adsorption process. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 .XRD spectra of Fe3O4, Fe3O4@SiO2, Fe3O4@SiO2-COOH, L-MIP and NIP involved in the material preparation process of Example 1 and Comparative Example 1.
[0024] Figure 2 .FT-IR spectra of Fe3O4, Fe3O4@SiO2, Fe3O4@SiO2-COOH, L-MIP and NIP involved in the material preparation process of Example 1 and Comparative Example 1.
[0025] Figure 3 .Evaluation of the selective adsorption properties of L-MIP and NIP prepared in Example 1 and Comparative Example 1.
[0026] Figure 4 .Analysis of magnetic properties of Fe3O4, Fe3O4@SiO2-COOH and L-MIP involved in the material preparation process of Example 1.
[0027] Figure 5 .TEM and SEM images of Fe3O4, Fe3O4@SiO2-COOH, and L-MIP involved in the material preparation process of Example 1.
[0028] Figure 6 .Distribution characteristic diagram of Fe, C, Si, and O elements of the L-MIP prepared in Example 1.
[0029] Figure 7 . Evaluation of the reusability of L-MIP prepared in Example 1 for limonin.
[0030] Figure 8 Evaluation of the effect of adsorption debittering of L-MIP prepared in Example 1 on the taste and quality of citrus juice.
[0031] Fig. 9 .Overall flow chart for the preparation of the limonin magnetic molecular imprinting material provided by the present invention. DETAILED DESCRIPTION
[0032] The present invention will be described in detail below in conjunction with the examples and accompanying drawings, and the advantages and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific embodiments and examples are used to illustrate the present invention, rather than to limit the present invention. The raw materials used in the following examples are obtained through commercial channels unless otherwise specified.
[0033] Example 1
[0034] A method for preparing a limonin magnetic molecular imprinting material comprises the following steps:
[0035] S1. Fe3O4@SiO2 magnetic microparticles: Mix 6 mL of tetraethyl orthosilicate and 50 mL of ethanol for use. Then, after fully mixing 350 mL of ethanol, 90 mL of water and 8 mL of NH3·H2O, add 1 g of Fe3O4 and disperse it evenly by ultrasound. Then, slowly drop the pre-prepared tetraethyl orthosilicate and ethanol mixture and mechanically stir at 50°C for 10 h. After the reaction is completed, separate the product by magnetic force, wash it repeatedly with ethanol and water, and vacuum dry it at 35°C for 12 h to obtain Fe3O4@SiO2 magnetic microparticles.
[0036] S2.Fe3O4@SiO2-COOH magnetic microparticles: 4g Fe3O4@SiO2 particles were ultrasonically dispersed in 320mL anhydrous toluene, and then 20mL 3-aminopropyltriethoxysilane was added and refluxed at 110°C for 12h under dry nitrogen. After the reaction, the obtained material was washed with toluene and DMF and uniformly dispersed in 300mL DMF, followed by the addition of 6g maleic anhydride. The obtained mixture was mechanically stirred at room temperature for 12h. The material was separated by magnetic force and washed with DMF three times to obtain Fe3O4@SiO2-COOH.
[0037] S3. Limonin magnetic molecular imprinting material: 0.5mmol limonin and 2mmol methacrylic acid were dispersed in 100mL acetonitrile and shaken for 6h for prepolymerization. Subsequently, 200mg Fe3O4@SiO2-COOH, 8mmol ethylene glycol dimethacrylate and 9.5mg azobisisobutyronitrile were added, and the mixed solution was purged with nitrogen for 10min under an ice bath and sealed. Then, a two-step temperature polymerization reaction was carried out in a constant temperature oscillator at a rate of 200r / min: first, polymerization at 50℃ for 6h, and then polymerization at 60℃ for 24h. After the reaction, the residual reagent on the surface of the obtained material was washed with acetonitrile, and then the template molecules therein were eluted with methanol-acetic acid (9:1, v / v). Finally, the material was rinsed with water and dried at 35℃ for 12h to obtain the limonin magnetic molecular imprinting material (L-MIP).
[0038] Comparative Example 1
[0039] A method for preparing a limonin magnetic non-molecular imprinted material comprises the following steps:
[0040] S1. Fe3O4@SiO2 magnetic microparticles: Mix 6 mL of tetraethyl orthosilicate and 50 mL of ethanol for use. Then, after fully mixing 350 mL of ethanol, 90 mL of water and 8 mL of NH3·H2O, add 1 g of Fe3O4 and disperse it evenly by ultrasound. Then, slowly drop the pre-prepared tetraethyl orthosilicate and ethanol mixture and mechanically stir at 50°C for 10 h. After the reaction is completed, separate the product by magnetic force, wash it repeatedly with ethanol and water, and vacuum dry it at 35°C for 12 h to obtain Fe3O4@SiO2 magnetic microparticles.
[0041] S2.Fe3O4@SiO2-COOH magnetic microparticles: 4g Fe3O4@SiO2 particles were ultrasonically dispersed in 320mL anhydrous toluene, and then 20mL 3-aminopropyltriethoxysilane was added and refluxed at 110°C for 12h under dry nitrogen. After the reaction, the obtained material was washed with toluene and DMF and uniformly dispersed in 300mL DMF, followed by the addition of 6g maleic anhydride. The obtained mixture was mechanically stirred at room temperature for 12h. The material was separated by magnetic force and washed with DMF three times to obtain Fe3O4@SiO2-COOH.
[0042] S3. Limonin magnetic molecular imprinting material: 2mmol methacrylic acid was dispersed in 100mL acetonitrile and shaken for 6h. Subsequently, 200mg Fe3O4@SiO2-COOH, 8mmol ethylene glycol dimethacrylate and 9.5mg azobisisobutyronitrile were added, and the mixed solution was purged with nitrogen for 10min under an ice bath and sealed. Then, a two-step temperature polymerization reaction was carried out in a constant temperature oscillator at a rate of 200r / min: first at 50°C for 6h, and then at 60°C for 24h. After the reaction, the residual reagent on the surface of the obtained material was washed with acetonitrile, and then the template molecules therein were eluted with methanol-acetic acid (9:1, v / v). Finally, the material was rinsed with water and dried at 35°C for 12h to obtain a limonin magnetic non-molecular imprinting material (NIP).
[0043] The XRD spectra of Fe3O4, Fe3O4@SiO2, Fe3O4@SiO2-COOH, L-MIP and NIP involved in the material preparation process of Example 1 and Comparative Example 1 are as follows: Figure 1As shown. Fe3O4@SiO2 shows a broad diffuse scattering peak in the range of 2θ=5°-30°, indicating that the coating of the SiO2 layer is successful. After loading the imprinting layer, L-MIP and NIP particles show the same XRD signal as Fe3O4 at 2θ=5°-30°. This consistency confirms that the crystal phase of the synthetic polymer is still Fe3O4, and the process of preparing the SiO2 layer and the MIP layer does not change the crystal structure of Fe3O4. These results also confirm that the various layer structures introduced during the preparation process mainly affect the surface chemical properties of the material, rather than its internal crystal structure.
[0044] The FT-IR spectra of Fe3O4, Fe3O4@SiO2, Fe3O4@SiO2-COOH, L-MIP and NIP involved in the material preparation process of Example 1 and Comparative Example 1 are shown in Figure 2 As shown. For Fe3O4, at 560cm -1 A characteristic peak appears at 959cm, which is attributed to Fe-O stretching vibration. -1 , 800cm -1 and 1087cm -1 The peaks at 452 cm are attributed to Si-OH, Si-O and Si-O-Si stretching vibrations. -1 The bands at 560 cm represent O-Si-O bending vibrations. The appearance of these peaks confirms the formation of the SiO2 layer. In addition, Fe3O4@SiO2 and Fe3O4@SiO2-COOH retain the 560 cm -1 The characteristic peak at 1728cm -1 and 2855cm -1 Two new absorption peaks appeared at 1154 cm -1 and 1254cm -1 The peaks at 1154 cm-1 and 1167 cm-2 correspond to the symmetric and asymmetric stretching vibrations of CO in the ester group, respectively. These functional groups are derived from methacrylic acid and ethylene glycol dimethacrylate, indicating that the MIP layer has been grafted onto the Fe3O4@SiO2 surface. It is worth noting that compared with L-MIP, NIP has a -1 and 1254cm -1 The peak at is weak, which indicates that the methacrylic acid and ethylene glycol dimethacrylate polymer layers in the NIP may lack sufficient cross-linking and order.
[0045] The selective adsorption performance of the materials prepared in Example 1 and Comparative Example 1 was evaluated. The specific experimental process was as follows: 0.3 mg / mL of different standards (including nomilin, nomilin, pyralidone, ursolic acid, oleanolic acid and pachymic acid) dissolved in a methanol-water (8:2, v / v) solution were respectively prepared; 15 mg of L-MIP and NIP prepared in Example 1 and Comparative Example 1 were weighed in a 10 mL round-bottom centrifuge tube, 3 mL of the prepared standard solution was added thereto, and after oscillation for 4 hours, the magnetic material was separated by an external magnetic field, and the clear liquid was taken and the content of the remaining standard was determined by high performance liquid chromatography; the equilibrium adsorption amount of the material for different components was calculated, and the results are as follows: Figure 3 The calculation formula of equilibrium adsorption capacity is as follows:
[0046]
[0047] Where Q e (mg / g) is the amount of sample adsorbed in 4 h; C i (mg / mL) and C f (mg / mL) are the initial and final concentrations of limonin, respectively; V (mL) is the volume of the solution; m (g) is the mass of the polymeric material (L-MIP or NIP).
[0048] Depend on Figure 3 It can be seen that the equilibrium adsorption amount of L-MIP (9.42±0.41mg / g) for limonin is higher than that of NIP (3.78±0.23mg / g), showing excellent selectivity. Since flavonoids have similar skeleton structure, functional groups and stereoscopic shape to limonin, they also have significant binding capacity on L-MIP (5.79±0.21mg / g). Although the structure of nomilin is very similar to that of limonin and flavonoids, its binding ability on L-MIP is relatively low (1.57±0.01mg / g). Its chemical structure shows that the position of one of the ester groups is significantly different from that of limonin, and the resulting stereoscopic difference may hinder the binding of nomilin in the L-MIP imprinting cavity. For oleanolic acid, ursolic acid and pachymic acid, although they and limonin are all triterpenoid compounds, they have weak binding ability on L-MIP because they do not have lactone structure. This also indirectly indicates that the lactone structure is of great significance for the specific recognition of L-MIP. For quercetin and hesperidin, which have significantly different skeleton structures, their binding amount on MIP is very low (0.12mg / g-0.34mg / g) due to the lack of various recognition elements. This shows that the prepared L-MIP does not have the specific recognition ability for these compounds except limonin, and at the same time verifies that the selectivity of molecular imprinting polymers depends on the structural characteristics of the template molecule.
[0049] The magnetic properties analysis results of Fe3O4, Fe3O4@SiO2-COOH and L-MIP involved in the preparation process of Example 1 are as follows: Figure 4 . The saturation magnetization values of Fe3O4, Fe3O4@SiO2 and L-MIP are 79.4emu / g, 42.2emu / g and 18.6emu / g, respectively. Obviously, with the increase of coating, the saturation magnetization intensity of the material gradually decreases. Nevertheless, even if the saturation magnetic susceptibility is reduced to 18.6emu / g, the L-MIP particles still show strong magnetism and can be quickly and completely separated from the mixture using an external magnetic field within 20s. In addition, none of the three particles showed hysteresis, and Fe3O4, Fe3O4@SiO2-COOH and L-MIP nanoparticles all showed superparamagnetic behavior, that is, in practical applications, the materials can quickly aggregate with or without an external magnet, which can significantly improve the convenience and efficiency of operation.
[0050] The TEM and SEM results of Fe3O4, Fe3O4@SiO2-COOH and L-MIP involved in the material preparation process of Example 1 are as follows: Figure 5 As shown. Fe3O4 (A, D) presents an almost spherical structure with a relatively smooth surface. In contrast, the Fe3O4@SiO2 (B, E) particles are larger in size and a distinct core / shell structure can be clearly observed. L-MIP (C, F) shows an irregular morphology characterized by a rough surface with obvious concave-convex features, which is the result of the formation of imprinted cavities.
[0051] The element distribution of L-MIP prepared in Example 1 is as follows: Figure 6 As shown in the figure. The strong Fe signal is concentrated in the core of the material, while the Si signal mainly appears on the outside of Fe in the form of an imprinted layer. At the same time, the C element signal shows a strong and uniform distribution throughout the material. The above results strongly confirm the success of the MIP coating.
[0052] The L-MIP prepared in Example 1 was evaluated for repeatability. The specific experimental process was as follows: L-MIP (15.0 mg) was dispersed in a solution of limonin (0.3 mg / mL, 3.0 mL) and shaken in a 25°C incubator for 240 min. The L-MIP was then separated and desorbed using methanol-glacial acetic acid (9:1, v / v). The adsorption-desorption process was repeated 8 times. The results are shown in Figure 2. Figure 7 shown.
[0053] Depend on Figure 7 It can be seen that after 7 regeneration cycles, L-MIP retained 90.03% of its initial adsorption capacity, showing its excellent stability.
[0054] The specific adsorption and debittering performance of L-MIP prepared in Example 1 was evaluated. The specific experimental process was as follows: 10 mL of clarified juice (Summer Orange, September Red and Late Night juice) and 50 mg of L-MIP particles were added to a 100 mL conical flask, and after oscillating for 4 hours at 25°C and 200 r / min, the L-MIP particles were separated from the juice by an external magnetic field. HPLC, electronic nose and electronic tongue were used to evaluate the changes in limonin content, nutrition, flavor and taste in the treated juice. The same treatment and analysis were used for commercial polystyrene divinylbenzene resin, and the juice that had not been debittered was used as a control. The results are shown in the figure. Figure 8 shown.
[0055] Depend on Figure 8 It can be seen that L-MIP can reduce the bitterness of juice by more than 69.21%. The results of electronic tongue showed that L-MIP treatment significantly reduced the bitterness of juice, and the overall flavor change was relatively small. At the same time, the retention rates of total flavonoids and ascorbic acid reached more than 75.68% and 82.30%, respectively, which were significantly higher than those of the resin treatment group, and had obvious selective adsorption performance.
[0056] Here, in order to facilitate a clearer understanding of the present invention, the overall process of the method of the present invention is now represented in the form of a diagram, see Fig. 9 .
[0057] The limonin magnetic molecular imprinted polymer prepared by the present invention has good specificity and selectivity in the adsorption process of limonin. When applied to the debittering treatment of citrus juice, it can not only efficiently remove limonin, but also effectively retain flavonoids and ascorbic acid in the juice, showing a significant debittering effect and showing good performance in maintaining the overall flavor and nutritional components.
[0058] The above embodiments of the present invention do not describe all the details in detail, nor limit the present invention to the above embodiments. Various changes, modifications, substitutions and variations made by ordinary technicians in this field without departing from the principles and purpose of the present invention should be included in the protection scope of the present invention.
Claims
1. A magnetic molecular imprinting material for selectively adsorbing limonin, characterized in that: The method comprises the following steps: S1.Fe3O4@SiO2 magnetic particles: After fully mixing the ethanol aqueous solution and NH3·H2O, add Fe3O4 and disperse it evenly by ultrasound. Slowly add the mixture of ethyl orthosilicate and ethanol and mechanically stir it at 50℃ for 10h. After the reaction is completed, separate the product by magnetic force, wash it repeatedly with ethanol and water, and vacuum dry it at 35℃ for 12h to obtain Fe3O4@SiO2 magnetic particles. S2.Fe3O4@SiO2-COOH magnetic particles: The Fe3O4@SiO2 prepared in S1 was dispersed in anhydrous toluene, ultrasonically mixed, and then 3-aminopropyltriethoxysilane was added. The mixture was refluxed at 110°C for 12 hours under dry nitrogen. After the reaction, the obtained material was washed with toluene and DMF, then evenly dispersed in DMF, and then maleic anhydride was added. The obtained mixture was mechanically stirred at room temperature for 12 hours. The obtained product was magnetically separated and washed with DMF three times to obtain Fe3O4@SiO2-COOH. S3. Limonin magnetic molecular imprinting material: Limonin and methacrylic acid were dispersed in acetonitrile and oscillated for 6 hours for prepolymerization. Then, Fe3O4@SiO2-COOH prepared in S2, ethylene glycol dimethacrylate and azobisisobutyronitrile were added, and the mixed solution was purged with nitrogen for 10 minutes under an ice bath and sealed. A two-step temperature polymerization reaction was carried out in a constant temperature oscillator at a rate of 200r / min: first, polymerization at 50°C for 6 hours, and then polymerization at 60°C for 24 hours. After the reaction, the residual reagents on the surface of the obtained material were washed with acetonitrile, and then the limonin therein was eluted with a mixture of methanol and acetic acid. Finally, the material was rinsed with water and dried at 35°C for 12 hours to obtain a limonin magnetic molecular imprinting material.
2. The limonin magnetic molecular imprinting material according to claim 1, characterized in that: The volume ratio of ethanol to water in the ethanol aqueous solution in S1 is 4:1; the volume of the ethanol aqueous solution is 0.45L / g based on the mass of Fe3O4; the amount of NH3 H2O is 8mL / g based on the mass of Fe3O4; the volume of tetraethyl orthosilicate is 6mL / g based on the mass of Fe3O4; and the volume ratio of tetraethyl orthosilicate to the ethanol mixed solution is 1:
10.
3. The limonin magnetic molecular imprinting material according to claim 1, characterized in that: The volume amount of toluene in the S2 is 80 mL / g based on the mass of the magnetic nano-microspheres Fe3O4@SiO2; the volume amount of 3-aminopropyltriethoxysilane is 5 mL / g based on the mass of the magnetic nano-microspheres Fe3O4@SiO2; the mass amount of maleic anhydride is 1.5 g / g based on the mass of the magnetic nano-microspheres Fe3O4@SiO2; and the volume amount of DMF is 80 mL / g based on the mass of the magnetic nano-microspheres Fe3O4@SiO2.
4. The limonin magnetic molecular imprinting material according to claim 1, characterized in that: The volume of acetonitrile in S3 is 200 mL / mmol based on the amount of the template molecule.
5. The limonin magnetic molecular imprinting material according to claim 1, characterized in that: The ratio of the amount of the template molecule, methacrylic acid and the cross-linking agent in S3 is 1:4:16; the mass amount of the initiator is 6 mg / g based on the mass of the cross-linking agent; the mass amount of Fe3O4@SiO2-COOH is 400 mg / mmol based on the amount of the template molecule; and the volume ratio of the methanol and acetic acid mixture is 9:
1.
6. A limonin magnetic molecular imprinting material as claimed in claim 1 for adsorbing limonin in citrus juice.
Citation Information
Patent Citations
Preparation method of magnetic zinc ion surface-imprinted polymer
CN103709341A
Preparation method of magnetic molecularly imprinted microspheres and application in separation and enrichment of cucurbitane triterpenoid
CN105921129A
Preparation method and application of magnetic molecularly imprinted nanoparticles for tetracycline
CN109666110A
Synthesis and application of A Nanomaterial for Removal of Patulin
US20190329221A1
Zearalenone functionalized graphene surface molecularly imprinted material, preparation method therefor and use thereof
US20230234029A1